Toward a Pedagogy of Dialogical Resistance - Foster, C. Rob (Paideusis, 2007)
Martin Buber provides an ethical understanding of dialogical resistance. But does this notion take sufficiently into account the oppositional force of resistance and the shifting realities of monologic relations? How are we to understand the terms dialogue and resistance? What impact will the ethics of dialogical resistance have on evaluation practices in public education? To address these questions, each term of this dyadic relationship must be defined. First I will differentiate dialogue from conversation, argument and discussion. Secondly it must be shown that my view of ethical resistance cannot be synonymous with criticism, disagreement or dissent per se, though undoubtedly certain connections do exist in practice. Then it will be appropriate to delve into a linguistic analysis of the substantive terms of dialogue and resistance as separate notions before using them together as intersecting concepts. Once I have delineated dialogical resistance as a dyadic tension, I will highlight Martin Buber's passion for human worth – the motivation for respect- as the necessary condition for the ethical success of dialogical resistance. The balance of this paper will take a look at the psychological roots of dialogical resistance, the complexity of practising dialogical resistance, and asymmetrical relations in the classroom.